2021
DOI: 10.1186/s12957-020-02115-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis analysis of patients with pancreatic neuroendocrine tumors after surgical resection and the application of enucleation

Abstract: Objective To investigate the prognostic factors of patients with pancreatic neuroendocrine tumor (pNETs) after surgical resection, and to analyze the value of enucleation for pNETs without distant metastasis that are well-differentiated (G1) and have a diameter ≤ 4 cm. Methods Data from pNET patients undergoing surgical resection between 2004 and 2017 were collected from the Surveillance, Epidemiology, and End Results (SEER) database. Kaplan–Meier … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
2
18
1
2
Order By: Relevance
“…CTC-positive, vascular invasion, nerve invasion, and lymph node metastasis are independent risk factors for postoperative recurrence, and the latter three variables have also been confirmed in past studies ( 33 38 ). CTC-positive, vascular invasion, and tumor size were independent risk factors affecting OS, which were also consistent with past reports ( 39 , 40 ). The above results show that peripheral blood CTCs play a pivotal role in DFS and OS in patients with pancreatic cancer.…”
Section: Discussionsupporting
confidence: 92%
“…CTC-positive, vascular invasion, nerve invasion, and lymph node metastasis are independent risk factors for postoperative recurrence, and the latter three variables have also been confirmed in past studies ( 33 38 ). CTC-positive, vascular invasion, and tumor size were independent risk factors affecting OS, which were also consistent with past reports ( 39 , 40 ). The above results show that peripheral blood CTCs play a pivotal role in DFS and OS in patients with pancreatic cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Based on previous literature (27,28), we divided the patients' age into >60 years old and ≤60 years old for convenient analysis. Although some researchers reported tumor site was an independent survival predictor of PC (29)(30)(31), our multivariate Cox regression analysis showed that tumor site was not correlated with OS or CSS in patients with PCBM. For convenient analysis, patients' tumor size were divided into<5 and ≥5 cm based on previous literature (21,28).…”
Section: Discussioncontrasting
confidence: 79%
“…Second, G3 neuroendocrine carcinomas are extremely rare and highly aggressive. 56 - 58 Therefore, findings in this study may not apply to all G3 cases. We also found that the prognostic value of our gene signature was diminished in G3 cases.…”
Section: Discussionmentioning
confidence: 84%